DIPLOMASI PUBLIK KOREA SELATAN MELALUI BTS DALAM MENDUKUNG SEKTOR PEREKONOMIAN DI BIDANG PASAR MUSIK GLOBAL 2019-2021 - Putri Alania Susanti (2023)
This study looks into the success of public diplomacy in South Korea by exploiting soft power features. The global population is highly invested in the Korean Wave phenomena. South Korean band BTS was able to use the Korean Wave as a tactical tool to carry out the country's public diplomacy mission. This study aims to examine BTS's public diplomacy efforts in strengthening the South Korean economy in the sphere of global music markets between 2019 to 2021. It explores the discussion utilizing the concepts of public diplomacy and the Korean Wave as basic the fundamentals. The research approach employed is a qualitative descriptive analytic method, with data collected through interviews, theoretical studies, and previous research. This study goes deeper into BTS's role as a non-state actor in carrying out South Korea's public diplomacy. Furthermore, this research shows a type of active participation from BTS to promote the advancement of the domestic economic sector and the formation of the country's image through its role in the expansion of Kpop songs in the worldwide music market through the 2019-2021 era.